HD 3059 (Pusa Pachheti): A new wheat variety for late sown irrigated conditions of north western plains zone of India - Singh, Shyam Sunder; Sharma, Jai Bhagwan; Singh, Pradeep Kumar; ., Vinod; Singh, Bhanwar; Prabhu, Kumble Vinod; Singh, Gyanendra Pratap; Sharma, Ram Kumar; Kumar, Dinesh; Kumar, Sanjay; Singh, Anju Mahendru; Yadav, Rajbir; et al. (Journal of Cereal Research, 2014)
A new bread wheat variety, HD3059 (Pusa Pachheti) has been released and notifed by the Central Sub- Committee on Crop Standards, Notifcation and Release of Varieties for Agricultural Crops, Government of India for commercial cultivation under late sown irrigated conditions of North Western Plains Zone (NWPZ) of the country. HD 3059 has average yield of 4.25 t/ha with yield potential of 5.94t/ha under late sown irrigated conditions and showed superiority over checks (PBW373, PBW 590 and WH 1021). It is resistant to yellow rust and brown rust. It has shown superior quality parameters with high protein content (13.6%), high sedimentation value (52ml), best Glu-1 Score (10/10) and good extraction rate (70.1%) meeting all the criteria for superior bread making qualities. This beingan early maturing variety has promise for late sown irrigated planting areas following basmati rice/wheat; potato/wheat and sugarcane/wheat cropping systems and thus will contribute to increasing wheat production in Indo-Gangetic region in India.